Metabolic Syndrome Is Associated With Poor Prognosis in Patients With Breast Cancer Receiving Neoadjuvant Therapy - Youzhao Ma; Jingyang Zhang; Dechuang Jiao; Xiuchun Chen; Zhenzhen Liu (Cancer Medicine)
ABSTRACT Purpose Few studies with a large sample size are available on patients with metabolic syndrome (MetS) receiving neoadjuvant treatment (NAT) for breast cancer. This study aimed to investigate the impact of MetS on the prognosis of patients with breast cancer undergoing NAT. Methods The data of patients with breast cancer receiving NAT at our center from January 2017 to December 2019 were retrospectively analyzed. A chi‐square test and logistic regression model were applied to ascertain the factors associated with MetS and pathological complete response (pCR). The Cox proportional risk model was employed for univariate and multivariate analyses of disease‐free survival (DFS) and overall survival (OS). Results Of the 910 patients enrolled, 164 (18.0%) were diagnosed with MetS, 568 (62.4%) with stage II, and 342 (37.6%) with stage III. Postmenopausal status (p = 0.045) and stage III (p = 0.009) were associated with a higher incidence rate of MetS. MetS was associated with a lower pCR rate (p = 0.027). The 5‐year DFS (83.7% vs. 73.1%, p = 0.001) and OS (92.8% vs. 85.5%, p = 0.001) of the non‐MetS group were significantly better than those of the MetS group. In premenopausal women, the DFS (p = 0.001) and OS (p = 0.025) of the non‐MetS group were significantly better than those of the MetS group. No significant differences were noted in DFS (p = 0.270) or OS (p = 0.078) between the two groups in postmenopausal women. In the Cox proportional risk model, MetS acted as an independent factor associated with DFS (HR = 1.705, 95% CI: 1.201–2.421, p = 0.003) and OS (HR = 1.874, 95% CI: 1.149–3.055, p = 0.012). Conclusion MetS was associated with poor prognosis in patients with breast cancer receiving NAT. Hence, close attention should be paid to patients with breast cancer who have MetS.